Макарычев алгебра 7 класс гдз

Номер 687

 

Условие:

Упростите выражение:
а) (Зb - 2) (5 - 2b) + 6b2; г) 5b3 + (a2 + 5b)(ab - b2);
б) (7y - 4)(2y + 3) - 13y;  д) (а - x)(а + 2) - (а + x)(а - 2);
в) x3 -(х2 - 3х)(х + 3);     е) (х + у)(х - у) - (х - 1)(х - 2).

Ответ:

a) (Зb - 2) (5 - 2b) + 6b2 = 15b - 6b2 - 10 + 4b + 6b2 = 19b - 10;
6) (7y - 4)(2y + 3) - 13y = 14y2 + 21y - 8y - 12 - 13y = 14y2 - 12;
в) x3 -(х2 - 3х)(х + 3) = x3 - x3 - 3x2 + 3x2 + 9x = 9x;
г) 5b3 + (a2 + 5b)(ab - b2) = 5b3 + a3b - a2b2 + 5ab2 - 5b3 = a3b - a2b2 + 5ab2;
д) (а - x)(а + 2) - (а + x)(а - 2) = a+ 2a - ab - 2b - a2 + 2a - ab + 2b = 4a - 2ab;
e) (х + у)(х - у) - (х - 1)(х - 2) = x2 - ху + ху - у2 - x2 + 2x + x - 2 = -y2 + 3x - 2.